Characteristics of Plastic Greenhouse High-Temperature and High-Humidity Events and Their Impacts on Facility Tomatoes Growth - Zhang, Qi; Zhang, Xinyu; Yang, Zaiqiang; Huang, Qinqin; Qiu, Rangjian (Frontiers in Earth Science, 2022)
Because of their relatively simple structures, plastic greenhouses in southern China have poor resistance to adverse external weather condition. Adverse meteorological condition inside the greenhouse is one of the main limiting factors for facility crop production in southern China. Among them, high temperature and high humidity often co-occurred in greenhouses, and induced great losses. Tomatoes (Lycopersicon esculentum Mill.) are grown under protected environment worldwide. Here, characteristics of high temperature and high humidity (HTHH) inside plastic greenhouses in southern China were analyzed and tomato was taken as the sample facility crop to study the effects of HTHH. Daily maximum temperature and average relative humidity (RH) inside plastic greenhouses were simulated by extreme learning machine (ELM) method to identify HTHH events. The results showed that the plastic greenhouse HTHH events mainly occurred from June to September in southern China, especially in southernmost region. During 1990 and 2019, the occurrence times and accumulative days of the HTHH events showed a downward trend at 0.3 times/decade and 2.6 d/decade, respectively, which is mainly due to their reduction in July. HTHH affected the growth of tomato, in which high temperature plays a more important role than high RH. Days of flower bud differentiation was more sensitive to HTHH stress than other physiological indexes of tomato. As the increase of the return period of the HTHH events, the corresponding losses of physiological indexes of tomato increased, except for western region, where the HTHH events rarely occurred. The results in this study could provide guidance for production and layout of greenhouse grown tomato, and the research approach can also be applied to other greenhouse grown crops and meteorological disasters.